Social Protection Benefits Compatibility and Evaluation Criteria: the Case of Lithuania - Gabnytė-Baranauskė, Vitalija (Ekonomika, 2024)
In general, the social protection (SP) system consists of two main blocks: social insurance (SI) and social assistance (SA). The main idea of SP is to leave no one behind, support in times of social risks. However, SI and SA systems are usually developed and improved separately. Organization for Economic Cooperation and Development (OECD) and European Commission (EC) often emphasise that expenditure on the SP system in Lithuania is scarce, income poverty and inequality are critical, not improving. This raises the question of whether both elements of SP in Lithuania are based on the same criteria to achieve consolidated SP and avoid its gaps. This paper aims to identify evaluation criteria, look at the Lithuanian SP system through its main benefits, and identify whether people are protected. The analysis consists of a literature review, which helps identify evaluation criteria for the SP system, and Lithuanian analysis based on evaluation criteria for 2018–2022 policy years. Three main criteria for SP benefits evaluation are identified: coverage, adequacy, and incentives to work. To make an in-depth analysis of the SP system in Lithuania, the tax-benefit microsimulation model EUROMOD is used to analyse different households’ poverty and unemployment traps and test whether the current SP system contributes to them. It was expected that this research would help to shed a light on how well Lithuanian SI and SA function simultaneously. Results show that SP system compatibility in Lithuania is above average, the weakest part is coverage.